2008
DOI: 10.1128/iai.01606-07
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Role of Paraoxonases in Inactivation of the Pseudomonas aeruginosa Quorum-Sensing Signal N -(3-Oxododecanoyl)- l -Homoserine Lactone

Abstract: The pathogenic bacterium Pseudomonas aeruginosa causes serious infections in immunocompromised patients. N-(3-Oxododecanoyl)-L-homoserine lactone (3OC12-HSL) is a key component of P. aeruginosa's quorum-sensing system and regulates the expression of many virulence factors. 3OC12-HSL was previously shown to be hydrolytically inactivated by the paraoxonase (PON) family of calcium-dependent esterases, consisting of PON1, PON2, and PON3. Here we determined the specific activities of purified human PONs for 3OC12-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 41 publications
4
118
0
3
Order By: Relevance
“…Interestingly, in addition to differential expression at various sites within the host (PON1 and PON3 are expressed in the liver and sera, whereas PON2 is a cell-associated enzyme expressed in various tissues [103]), the different PON enzymes appear to have unique enzymatic activities. All three purified PONs had AHL lactonase activity in vitro, but each enzyme was determined to have a distinct specificity against a range of substrates, with PON1 and PON3 acting on the widest range of substrates but PON2 being the most active against AHLs (76,(103)(104)(105). In vitro results have supported a role for PON2 in AHL degradation by murine tracheal epithelial cells (104), and other experiments have demonstrated that both serum PON1 and purified PON1 reduce P. aeruiginosa biofilm formation in vitro (103).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 50%
“…Interestingly, in addition to differential expression at various sites within the host (PON1 and PON3 are expressed in the liver and sera, whereas PON2 is a cell-associated enzyme expressed in various tissues [103]), the different PON enzymes appear to have unique enzymatic activities. All three purified PONs had AHL lactonase activity in vitro, but each enzyme was determined to have a distinct specificity against a range of substrates, with PON1 and PON3 acting on the widest range of substrates but PON2 being the most active against AHLs (76,(103)(104)(105). In vitro results have supported a role for PON2 in AHL degradation by murine tracheal epithelial cells (104), and other experiments have demonstrated that both serum PON1 and purified PON1 reduce P. aeruiginosa biofilm formation in vitro (103).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 50%
“…This is an important function that may link paraoxonases to innate immunity, as lactonases can act as quorum quenching agents to limit bacterial virulence. It has been clearly demonstrated that the paraoxonases, by hydrolysis of HSL, limit infection and biofilm formation by Pseudomonas aeruginosa [34]. All three members of the paraoxonase gene family can neutralize HSL, with paraoxonase-2 being the most active [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated that the paraoxonases, by hydrolysis of HSL, limit infection and biofilm formation by Pseudomonas aeruginosa [34]. All three members of the paraoxonase gene family can neutralize HSL, with paraoxonase-2 being the most active [34]. However, it is an intracellular enzyme, and under conditions where diffusion of HSLs into cells may be rate limiting for their inactivation activity, PON1 assumes greater importance [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the intracellular PON2 variant shows the strongest lactonase activity, PON1is also active towards HSL (Ozer et al 2005) and is able to protect against Pseudomonas infection (Stoltz et al 2008). Indeed, PON1 is the major source of HSL neutralising activity in serum (Teiber et al 2008). …”
Section: Pon1 and Bacterial Pathogensmentioning
confidence: 99%